(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Every poetic or rhetorical literary text contains, in addition to its dominant function, other functions, such as: emotion, guidance, and persuasion. The poetic text is not only imagination and an individual, subjective experience, but it seeks to encourage, incite, persuade, and argue, and to change attitudes and behavior. Arguments are a linguistic phenomenon present in every statement and every speech, and whoever the speaker is, the conversation must be subject to Aristotle’s triangle with its three sides: ethics (ethos), the emotion used ((pathos), and logic (logos). Because we will try to study arguments from the angle of the emotional dimension, it is necessary Focusing on the aspect of emotion, taking into account Aristotle’s statement that persuasion may come from the listeners when the sermon stirs their feelings, and Ibn Zaydun’s poem under study is full of intense emotion and plays on the strings of emotions as a means of argument and persuasion.